Overweight and obesity trends in Mexican children 2 to 18 years of age from 1988 to 2006 Tendencias de sobrepeso y obesidad en niños mexicanos de 2 a 18 años de edad: 1988 a 2006 - Anabelle Bonvecchio; Margarita Safdie; Eric A Monterrubio; Tiffany Gust; Salvador Villalpando; Juan A Rivera (Instituto Nacional de Salud Pública, 2009)
OBJECTIVE: To describe prevalences and trends of overweight and obesity/OW&OB in Mexican children from 1988 to 2006 at the national level and by relevant subpopulations. MATERIAL AND METHODS: Prevalences of OW&OB in children aged 2-18 years were estimated using body mass index data from three national surveys conducted in 1988, 1999 and 2006. RESULTS: Prevalences of OW&OB are high in children of all ages, particularly among school-age and adolescent groups disaggregated by regions, socioeconomic status, urban and rural areas, and ethnic groups. The overall prevalence of OW&OB in children 2 to 18 years old in 2006 was 26.3%. Prevalences by age groups were 16.7% in preschool-age, 26.2% in school-age, and 30.9% in adolescents, using the IOTF classification system. CONCLUSIONS: Upward trends were observed in school-age children and adolescents at the national level and in all subpopulations. OBJETIVO: Describir las prevalencias y tendencias de sobrepeso y obesidad (SPyO) en niños mexicanos, de 1988 a 2006, en el ámbito nacional y por subgrupos relevantes de población. MATERIAL Y MÉTODOS: Las prevalencias de SPyO (peso no saludable) se estimaron usando cifras de índice de masa corporal de tres encuestas nacionales realizadas en 1988, 1999 y 2006. RESULTADOS: Las prevalencias de SPyO son altas en niños de todas las edades, particularmente en niños de edad escolar y adolescentes, estratificados por regiones, estado socioeconómico, áreas urbanas, rurales y grupo étnico. La prevalencia de SPyO en 2006 fue de 26.3% en el grupo de entre 2 a 18 años de edad, 16.7% en preescolares, 26.2% en escolares y 30.9% en adolescentes, usando la clasificación de The International Obesity Task Force (IOTF). CONCLUSIONES: Se observa una tendencia de sobrepeso y obesidad en aumento en niños de edad escolar y adolescentes, para todos los subgrupos de población.